Pusat Asuhan Kanak-Kanak Kids World Sdn. Bhd. / Nurul Syafina Hamzah ... [et al.] - Hamzah, Nurul Syafina; Fauzi, Nurrullaily; Mat Shahar, Normasita; Mohd. Latif, Eliana (Faculty of Civil Engineering, 2005)
KIDS WORLD SDN. BHD. is one of the private limited Company business which incorporated under the Company Act 1965 and generated by four young, determine entrepreneurs. It will be formed on 15* January 2006. The business' accumulated RM 107,106 as the start-up capital and it is expected to generate a profit of RM 1, 553 for the first year of Operation and increase to RM 6,782 during second year and to RM 14,525 during third year.